2017
DOI: 10.1097/inf.0000000000001574
|View full text |Cite
|
Sign up to set email alerts
|

Child Growth According to Maternal and Child HIV Status in Zimbabwe

Abstract: Background:Growth failure is common among HIV-infected infants, but there are limited data on the effects of HIV exposure or timing of HIV acquisition on growth.Methods:Fourteen thousand one hundred ten infants were enrolled in the Zimbabwe Vitamin A for Mothers and Babies trial in Zimbabwe before the availability of antiretroviral therapy or co-trimoxazole. Anthropometric measurements were taken from birth through 12–24 months of age. Growth outcomes were compared between 5 groups of children: HIV-infected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
63
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 42 publications
7
63
0
1
Order By: Relevance
“…These infants did not have the elevated WLZ observed in our population. In Zimbabwe before the availability of ART, HEU infants had higher risk of stunting and wasting, but growth trajectories in LAZ and WLZ were not meaningfully different from unexposed infants over the first 2 years of life (Omoni et al, ). HEU infant WLZ was lower than unexposed infants WLZ in this setting, whereas we find that HEU infant WLZ is higher than the average WLZ of Rwanda as a whole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These infants did not have the elevated WLZ observed in our population. In Zimbabwe before the availability of ART, HEU infants had higher risk of stunting and wasting, but growth trajectories in LAZ and WLZ were not meaningfully different from unexposed infants over the first 2 years of life (Omoni et al, ). HEU infant WLZ was lower than unexposed infants WLZ in this setting, whereas we find that HEU infant WLZ is higher than the average WLZ of Rwanda as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…Option B+ was quickly adopted in Rwanda, where it was implemented in 2013. Before Option B+ and the WHO recommendation for continued breastfeeding of HEU infants, HEU infants were at higher risk of impaired growth than their unexposed counterparts (Evans et al, ; Lartey et al, ; Omoni et al, ). The prevalence of risk factors for poor growth associated with HIV is expected to decrease with the adoption of Option B+ and the WHO recommendation for continued breastfeeding among HIV‐positive mothers in low‐resource settings (Evans et al, ; WHO, ).…”
Section: Introductionmentioning
confidence: 99%
“…We found that infants born to mothers with more than primary education or of taller stature experienced less linear growth decline compared with those with less educated and shorter mothers. Maternal education is consistently associated with improved childhood growth in SSA (Omoni et al, ; Webb et al, ). Among HIV‐infected mothers, those with more schooling may have greater knowledge regarding health care seeking, and adherence to medical advice, each of which may help to protect the health of the mother and her infant.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, 15.2 million children were CHEU worldwide, thus exposed to HIV and ARV [ 6 ]. Many unfavourable health outcomes have been reported in CHEU such as metabolic disorders [ 7 , 8 ], increased infectious disease morbidity and higher mortality [ 9 , 10 , 11 , 12 ], impaired growth [ 13 , 14 , 15 , 16 , 17 , 18 ], neurodevelopmental delays [ 17 , 19 , 20 , 21 ], altered immunity [ 10 , 22 , 23 , 24 , 25 , 26 ], and mitochondrial toxicity in comparison to never HIV-exposed children [ 27 , 28 , 29 , 30 ]. Taken together, this prompted Powis and Siberry to advocate for the long-term follow up of CHEU irrespective of their HIV/ARV exposures [ 31 ].…”
Section: Introductionmentioning
confidence: 99%